Economical Fishing Ground of Small-Scale Floating Lift Net Fishery Fleet in Every Season in Small Island Park Conservation Area, Southeast Maluku Regency - Picaulima, Simon M.; Makailipessy, Marvin M.; Thenu, Imanuel M. (Agrikan: Jurnal Agribisnis Perikanan, 2024)
The fishing ground of the floating lift net fishing fleet in each season in the TPK Kei Kecil conservation area has different economic value because the number of catches, fleet income, and operational costs of the fleet operating in the fishing ground of Ngaf-Ohoiew Island, Sepuluh Island, and Lima Island in each season is different. This study aims to analyze the economic fishing ground of the floating lift net fishing fleet in each season in the region. The locations of this research are Ohoi Namar, Ohoi Selayar, Ohoi Ohoililir, and Ohoi Dian Island, and it will be carried out in May – Oktober 2023. Data was collected using the survey method; respondents were determined using purposive sampling. The data that has been collected includes fishing ground, catches, fleet revenues, and fleet operational costs, then analyzed descriptively, qualitatively, and quantitatively, then presented in the form of pictures. The study recommends that the economical floating lift net fishing fleet fishing area in the TPK Kei Kecil conservation area in transition season 1 and 2 is a fishing ground located in the waters of Ngaf-Ohoiew Island because it has a high income from operational costs of Rp 136,059,000 in transition season 1 and Rp 126,420,000 in transition season 2, respectively while in the eastern season is the fishing ground in the waters of Pulau Lima because the average income is Rp 157,669,000.